2011
DOI: 10.1180/minmag.2011.075.1.87
|View full text |Cite
|
Sign up to set email alerts
|

The compositional variability of eudialyte-group minerals

Abstract: Eudialyte-group minerals (EGM) represent the most important index minerals of persodic agpaitic systems. Results are presented here of a combined EPMA, Mössbauer spectroscopy and LA-ICP-MS study and EGM which crystallized in various fractionation stages from different parental melts and mineral assemblages in silica over- and undersaturated systems are compared. Compositional variability is closely related to texture, allowing for reconstruction of locally acting magmatic to hydrothermal processes. Early-magma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 55 publications
2
68
0
1
Order By: Relevance
“…These differences are also found in the bulk composition of the EGM-bearing nepheline microsyenite dyke (Table 1), which suggests that EGMs crystallized in an environment where Eu, Sr, and Ba were already depleted. This depletion could be assigned to previous extensive fractionation of plagioclase and/or alkali feldspar (e.g., Blundy & Wood 1991, Bédard 2006, Brotzu et al 2007, Henderson & Pierozynski 2012, Carvalho & Janasi 2012) from the parental melt, similar to the interpretation by Schilling et al (2011b) regarding the same features observed in the EGMs from Ilímaussaq and Mont Saint-Hilaire.…”
Section: Petrologic Implicationssupporting
confidence: 53%
See 4 more Smart Citations
“…These differences are also found in the bulk composition of the EGM-bearing nepheline microsyenite dyke (Table 1), which suggests that EGMs crystallized in an environment where Eu, Sr, and Ba were already depleted. This depletion could be assigned to previous extensive fractionation of plagioclase and/or alkali feldspar (e.g., Blundy & Wood 1991, Bédard 2006, Brotzu et al 2007, Henderson & Pierozynski 2012, Carvalho & Janasi 2012) from the parental melt, similar to the interpretation by Schilling et al (2011b) regarding the same features observed in the EGMs from Ilímaussaq and Mont Saint-Hilaire.…”
Section: Petrologic Implicationssupporting
confidence: 53%
“…Most of the trace element contents of the EGMs from Monte de Trigo vary within the ranges of EGMs from other localities (Wu et al 2010, Schilling et al 2011b, especially the HFSEs and REE. Major differences of the analyzed EGMs include low-Sr and Ba contents and a negative Eu/ Eu* ratio (Fig.…”
Section: Petrologic Implicationsmentioning
confidence: 99%
See 3 more Smart Citations